Plasmonic Hot-Electron Reactive Oxygen Species Generation: Fundamentals for Redox Biology - Carrasco, Elisa; Stockert, Juan Carlos; Juarranz, Ángeles; Blázquez-Castro, Alfonso (Frontiers in Chemistry, 2020)
For decades, the possibility to generate Reactive Oxygen Species (ROS) in biological systems through the use of light was mainly restricted to the photodynamic effect: the photoexcitation of molecules which then engage in charge- or energy-transfer to molecular oxygen (O2) to initiate ROS production. However, the classical photodynamic approach presents drawbacks, like per se chemical reactivity of the photosensitizing agent or fast molecular photobleaching due to in situ ROS generation, to name a few. Recently, a new approach, which promises many advantages, has entered the scene: plasmon-driven hot-electron chemistry. The effect takes advantage of the photoexcitation of plasmonic resonances in metal nanoparticles to induce a new cohort of photochemical and redox reactions. These metal photo-transducers are considered chemically inert and can undergo billions of photoexcitation rounds without bleaching or suffering significant oxidative alterations. Also, their optimal absorption band can be shape- and size-tailored in order to match any of the near infrared (NIR) biological windows, where undesired absorption/scattering are minimal. In this mini review, the basic mechanisms and principal benefits of this light-driven approach to generate ROS will be discussed. Additionally, some significant experiments in vitro and in vivo will be presented, and tentative new avenues for further research will be advanced.